THE INFLUENCE OF EMOTIONAL MARKETING ON PURCHASE INTENTION WITH WORD OF MOUTH AS A MODERATING VARIABLE - Alya Elita Sjioen; Hadiansyah Ma’sum; Eva Yuniarti Utami; Dewi Endah Fajariana; Andriya Risdwiyanto (CV. Adiba Aisha Amira, 2025)
Backgrounds: Consumer purchasing decisions are something that a seller looks forward to because the more consumers who decide to buy, the healthier the company selling the product will be. There are several things that can influence purchasing decisions, including marketing emotions and word of mouth communication with good information. Objectives: Therefore, this research aims to analyze the influence of marketing emotions on purchasing decisions with word of mouth as a moderating variable. Methods: This research is quantitative research with an explanatory approach (Supriyanto, 2019). The data in this research was obtained through distributing online questionnaires to buyers from building partners spread throughout Indonesia consisting of 100 consumers and 200 producers. Such data can be called primary data (Farrell, 2016). These primary data were analyzed using the smart PLS 4.0 analysis tool. Results and Conclusions: Emotional Marketing variable can have a positive relationship direction and a significant influence on Purchasing Decisions due to the PV-value alues leads to positive and is below the significance level of 0.05, namely 0.039. Apart from that, the Word of Mouth variable can moderate the influence of the Emotional Marketing variable on Purchase Decision because the p-Values value is positive and is below the 0.05 significance level.